2017
DOI: 10.1093/bja/aex219
|View full text |Cite
|
Sign up to set email alerts
|

Alternative technique or mitigating strategy for sevoflurane-induced neurodegeneration: a randomized controlled dose-escalation study of dexmedetomidine in neonatal rats

Abstract: We confirm previous findings of sevoflurane-induced neuronal injury. Dexmedetomidine, even in the highest dose, did not cause similar injury, but provided lesser degrees of anaesthesia and pain control. No mitigation of sevoflurane-induced injury was observed with dexmedetomidine supplementation, suggesting that future studies should focus on anaesthetic-sparing effects of dexmedetomidine, rather than injury-preventing effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 46 publications
2
50
0
Order By: Relevance
“…Moreover, DEX has neuroprotective effects in the hypoxic‐ischemic neonatal brain (Ren et al, 2016; Zhou et al, 2018) and in an acute hyperoxic neonatal rat model (Endesfelder et al, 2017; Sifringer et al, 2015). In contrast, DEX does not ameliorate the injury induced by sevoflurane, and induces neural apoptosis in neonatal rats (Lee et al, 2017). Although many reports have shown that DEX is protective against anesthesia‐induced neurodegeneration, few reports have shown high mortality rates under high‐dose DEX with sevoflurane anesthesia in neonatal rats (Lee et al, 2017; Perez‐Zoghbi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, DEX has neuroprotective effects in the hypoxic‐ischemic neonatal brain (Ren et al, 2016; Zhou et al, 2018) and in an acute hyperoxic neonatal rat model (Endesfelder et al, 2017; Sifringer et al, 2015). In contrast, DEX does not ameliorate the injury induced by sevoflurane, and induces neural apoptosis in neonatal rats (Lee et al, 2017). Although many reports have shown that DEX is protective against anesthesia‐induced neurodegeneration, few reports have shown high mortality rates under high‐dose DEX with sevoflurane anesthesia in neonatal rats (Lee et al, 2017; Perez‐Zoghbi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DEX does not ameliorate the injury induced by sevoflurane, and induces neural apoptosis in neonatal rats (Lee et al, 2017). Although many reports have shown that DEX is protective against anesthesia‐induced neurodegeneration, few reports have shown high mortality rates under high‐dose DEX with sevoflurane anesthesia in neonatal rats (Lee et al, 2017; Perez‐Zoghbi et al, 2017). Thus, the efficiency of DEX against sevoflurane‐induced neurodegeneration is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The changes seen in preclinical studies are greatest with exposure to gamma‐aminobutyric acid (GABA) agonists and N‐methyl‐D‐aspartate (NMDA) antagonists such as volatile anesthetics (eg, sevoflurane), propofol, midazolam, ketamine, and nitrous oxide. There is less evidence for such changes with opioids (eg, remifentanil) and conflicting evidence with alpha‐2 agonists (eg, dexmedetomidine), with neurodegeneration occurring with doses larger than those used clinically . Furthermore, these preclinical studies showed a dose‐response relation: higher doses of anesthesia (ie, longer anesthesia) are associated with more morphologic and functional changes.…”
Section: Introductionmentioning
confidence: 99%
“…The total dose of dexmedetomidine per animal ranged from 2 to 525 µg/kg. In 17 studies, dexmedetomidine was administered in combination with another anesthetic agent, including ketamine (75 mg/kg intraperitoneal or intravenous infusion at 20 to 50 mg/kg/h for a period of 12 hours), propofol (intraperitoneal 30 mg/kg/d for a period of 7 days to 100 mg/kg and 1.2 mg/kg/min as continuous infusion for 6 hours), and inhalation anesthetic (isoflurane 0.75%‐2.0%, sevoflurane 2.5%‐4% up to 6 hours) …”
Section: Resultsmentioning
confidence: 99%
“…The effects of dexmedetomidine alone on caspase‐3 activity were investigated in eight studies (Tables and ) . Detection of caspase‐3 enables to identify neurons that are undergoing apoptotic degeneration.…”
Section: Resultsmentioning
confidence: 99%